(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
Numerical investigation of multiple shock/turbulent flow interaction is carried out using large eddy simulation for a supersonic channel flow with an inlet free stream Mach number 1.61. Various fundamental mechanisms dictating the flow phenomena including shock train, shear layer and turbulence behavior are investigated. It is found that the existence of the shock train and separated shear layer has an important influence on turbulence features. The turbulence intensities and turbulent kinetic energy (TKE) are strengthened in the region of the multiple shock because of the unsteadiness of the shocks. The investigation on the transport equations of the TKE and the pressure fluctuation reveals that the multiple shock and the roll-up vortices of shear layer can promote the generation of the TKE and the pressure fluctuation. The unsteady behavior of flow field is further analyzed by means of the proper orthogonal decomposition method. It is found that the multiple shock and the separated shear layer dominate the unsteady feature.